Implementasi Kebijakan Publik dalam Penanganan Covid-19 melalui Pendekatan Keagamaan : Public Policy Implementation in Handling Covid-19 through a Religious Approach - Robi Sugara; Maria Ulfa (Direktorat Jenderal Bimbingan Masyarakat Islam, 2021)
This article discusses the implementation of the Indonesian government's public policies in handling Covid-19 through a religious approach, especially through Islamic councelors. The purpose of this study is to explain the implementation of government policies in handling Covid-19 from the religious aspect carried out by Islamic councelors in Indonesia. This descriptive-analytical qualitative research uses videos published by Islamic councelors related to the handling of Covid-19 on Youtube media in April 2020 - March 2021 as the main source. Data analysis uses inductive method with the perspective of public policy implementation. The results of this study show that the implementation of the Indonesian government's policies regarding the handling of Covid-19, especially with a religious approach through Islamic councelors, has so far been carried out with various activities and socialization offline and online including through Youtube videos from various regions in Indonesia. The implementations of the Covid-19 handling policy carried out by Islamic councelors have covered basic matters based on several existing policies. The works of Islamic councelors have greatly contributed to the handling of Covid-19 in the field of religious matters, however Islamic councelors still need encouragement from the government to enhance the capacity to use social media, digital technology, media literacy, and digital literacy to reach wider benefits particularly during the pandemic.